NECK FUNCTION IN ELITE MALE RUGBY UNION PLAYERS: RESULTS FROM A PILOT FOR AN INTERVENTION STUDY. Issue 4 (1st February 2017) - Zietsman, Bianca; Holth, Espen Aag; McCarthy, Peter
Abstract : Background: Elite male rugby union players have a decreased active cervical spine rage of motion (ACROM), the severity correlates to both number of years playing and position (Lark & McCarthy 2007, Scher 1990), but a measurable decrease occurs over a season (Lark & McCarthy 2010). Objective: The aim was to ascertain whether a neck prehabiliation protocol, using body weighted suspension bands (FKPro), could affect the expected attrition in cervical spine function. Design: ACROM of all participants was measured with a CROM device (Capuano-Pucci et al 1991), using a Latin square randomisation to eliminate order effects. Likert scale questionnaires were also provided to all participants (pain and associated symptomatology). Setting: A clinical setting within semi professional Welsh Rugby Union Club. Participants: 19 participants were recruited from Beddau RFC first XV. All players were included in the study, unless the player was ruled out from training or playing for clinical reasons. Height 181.5 (±5.9) cm, weight 98.7 (±17.2 kg, age 23.9 (±4.2) yrs. Interventions (or Assessment of Risk Factors): Participants underwent a progressive 8 week intervention, using the FKPRO with neck harness. Postural and isometric holds were performed of 30 seconds duration in four directions under clinical supervision twice weekly (training days). Main Outcome Measurements: Change in ACROM. Results: Conclusions: The apparent lack of decrease in ACROM (i.e. no statistical difference) could indicate that the prehabilitation protocol helps compensate for the effects of participation in the contact sport on the cervical spine of athletes. A full study (duration of the playing season) is currently underway.